2015
DOI: 10.3233/wor-152205
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in caregiver strain, needs for support, social support, and quality of life among spousal caregivers of persons with multiple sclerosis

Abstract: MS caregivers experience significant strain that diminishes quality of life. Social support and needs fulfillment can act to buffer this stress; however, results indicate that this varies by gender, with gender differences observed in strain, perceived support, and expressed needs among MS caregivers. The study implications for rehabilitation research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…Female family members of critically ill patients had higher information, proximity, comfort, and support needs, compared to male family members. These results consistent with previous study [37] that reported female caregivers may feel more obligated and expected to fulfill a wide variety of caregiving roles.…”
Section: Plos Onesupporting
confidence: 93%
“…Female family members of critically ill patients had higher information, proximity, comfort, and support needs, compared to male family members. These results consistent with previous study [37] that reported female caregivers may feel more obligated and expected to fulfill a wide variety of caregiving roles.…”
Section: Plos Onesupporting
confidence: 93%
“…It was evident from the results, as previously reported (Lee et al, 2013;Lehan et al, 2012), that providing care to a person with a debilitating neurological condition, such as MS, is highly stressful and caregivers o f these people face several challenges throughout the caregiving process. However, caregivers prioritise the needs of the patient they care for above their own health (Bevans & Sternberg, 2012) and most o f the participants in this study demonstrated extreme willing ness to endure and sacrifice for the people they care for.…”
Section: Discussionmentioning
confidence: 52%
“…Akku §, 2011; Bevans & Sternberg, 2012;Bogosian et al, 2009;Given et a l, 2012;Khan et a l, 2007;Lee et al, 2013;Papastavrou et al, 2012;Smedman 2012), a number of resources have been identified to make caregiving easier (e.g. Bjorgvinsdottir & Halldorsdottir, 2014;Given et a l, 2012;Koopman et al, 2006;Lehan et al, 2012;O'Connor & McCabe, 2011;Peters et al, 2013;Smedman, 2012).…”
Section: Resources Available To Caregiversmentioning
confidence: 97%
See 1 more Smart Citation
“…Positive correlation interconnections between depression level and depressive and denial control strategies are revealed (Lee, Dedios, Fong, Simonette, & Lee, 2013;Mikula, Nagyova, Krokavcova, Vitkova, Rosenberger, Szilasiova, Van Dijk, 2014;Busch, Spirig, & Schnepp, 2014). Cognitive deficit growth of MS patients provokes the growth of depression level irrespective of specific control types (Haase et al, 2008).…”
Section: Relevancementioning
confidence: 99%